Bulletin No. 39. The Geology of Cook County Minnesota - Grout, Frank F.; Sharp, Robert P.; Schwartz, George M. (Minnesota Geological Survey, 1959)
Seventeen map inserts as pdfs, scales from 1:24,000 to 1:300,000. Cook County covers a triangular-shaped area at the extreme northeastern tip of Minnesota between Lake Superior on the south and the province of Ontario, Canada on the north. Its area is approximately 1680 square miles, of which about 274 square miles is covered by several hundred lakes. Its position north of Lake Superior is responsible for a rather moist and cool climate favorable to the growth of timber rather than agriculture. As a result, most of the area is covered by second-growth forest and this, together with the numerous rock-bound lakes, makes it an important vacation area. The area is hilly with a minimum elevation above sea level of 602 feet at Lake Superior and 2232 feet in the Misquah Hills. Much of the northern part of the county is characterized by long narrow lakes separated by prominent ridges. The geology is controlled, in a broad way, by its position on the north limb of the Lake Superior syncline. With the exception of glacial deposits the rocks are all of Precambrian age, with the youngest in a general way occurring along the coast of Lake Superior and the oldest in the Gunflint district and near Saganaga Lake. The older rocks consist of the Ely greenstone, Saganaga granite and Knife Lake group of slates, graywackes, metamorphosed tuffs and various minor types. These form an area of exceedingly complex geology, limited to four townships at the northwest corner of the county. The next group in age, commonly called the Animikie rocks, consists of a thin quartzite followed by the Gunflint iron formation and this, in turn, by the Rove formation. These are correlated with the Biwabik iron formation and Virginia formation of the Mesabi district. The Gunflint formation is mainly limited to two of the four northwest townships noted above, but the Rove formation forms a narrow belt along the international boundary from Gunflint Lake to Pigeon Point, a distance of seventy miles. The beds of the Rove formation dip southward at low angles and have been intruded by numerous diabase sills. Erosion has left the sills standing as asymmetrical ridges between valleys occupied by long narrow lakes. Over two thirds of the county is underlain by rocks of Keweenawan age, consisting of a thin sandstone and conglomerate at the base overlain by an exceedingly thick series of lava flows. These, in turn, are intruded by the eastern part of the huge Duluth gabbro complex and by an extensive series of diabase sills, dikes, and irregular intrusions. The lava flows consist mainly of somewhat variable basalt plus a much smaller percentage of rhyolite. The oldest flows crop out near Grand Portage Bay and trend inland so that successive flows occur along shore to the west as far as Tofte, where the sequence is reversed. A total of 92 flows were mapped between Grand Portage and Tofte with an estimated thickness of over seventeen thousand feet. In the northwestern part of the gabbro exposed in Cook County there is a group of three granite and granodiorite masses of somewhat uncertain origin, but apparently of later age than the gabbro. During Pleistocene time glaciers probably invaded Cook County several times, but the drift now exposed to view represents deposits from the Rainy Lobe, which probably covered the entire county, and the Superior Lobe which covered only a narrow strip along Lake Superior. Drift is of sufficient thickness in some parts of the county to rather effectively mask the underlying rocks and leave unanswered questions about their detailed relations. Glacial lakes covered parts of the county during the waning stages of the glaciers and left abandoned beaches at several levels, as well as glacial-lake clay soils. In spite of the complex geology, Cook County has not furnished productive mineral deposits. Deposits of iron formation, titaniferous magnetite, copper sulfides, and lesser nickel and cobalt sulfides have been investigated from time to time. Forest resources and the resort business are the main sources of revenue, but fishing in Lake Superior and limited agriculture have added to the income. Recently the establishment of Taconite Harbor and a steam power plant by the Erie Mining Company at the end of their railroad from the Mesabi district has been an important addition to the economy.